Multi-objective optimization of process parameters of Fused Deposition Modeling (FDM) for printing Polylactic Acid (PLA) polymer components. (2021) - Patil, Pooja; Singh, Dharmendra; Raykar, Sunil J.; Bhamu, Jaiprakash
Abstract: Additive Manufacturing (AM) which is also known as 3D printing is radical approach of manufacturing highly accurate components with polymers, metals and composites. It builds products by adding material layer by layer. Due to its capability of producing any complex shape with help of a 3D CAD model, it is gaining huge importance and significance in industrial sector. It has applications in manufacturing, medical, automobile, aerospace, construction, product development and many other sectors. Fused Deposition Modeling (FDM) is one of the widely used such AM process to build polymer components of simple to intricate shapes. To enhance the performance of FDM, it is very essential to have a proper set of input parameters like the layer thickness, infill %, infill pattern, temperature, printing speed and other parameters. In this investigation Multi-objective optimization paradigm to optimize process parameters of FDM for printing of Polylactic Acid (PLA) components is presented. Infill patterns, infill %, printing speed and layer thickness are the parameters used for investigation. Infill pattern is the process parameter of main focus in this investigation. Surface roughness, Printing time and Filament length consumed are responses used for analysis. Triangles pattern, infill % of 70%, printing speed of 100 mm/h and layer thickness of 0.2 mm are the optimum parameters for this investigation.